2019
DOI: 10.1007/s13224-019-01213-7
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Disorders and Menopause

Abstract: Menopause has an adverse impact on overall musculoskeletal health. It is associated with osteoporosis, osteoarthritis and Sarcopenia. Sarcopenia includes age-related muscle wasting as well as loss of muscle function. It is a relatively newly recognized condition and is known to be accelerated by estrogen deficiency. Osteoarthritis is also linked with estrogen deficiency more recently. Locomotor disability leads to a compromised quality of life. Sarcopenia and obesity (sarcobesity) have adverse outcome as it le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 25 publications
0
41
0
1
Order By: Relevance
“…It is possible that differential EV protein cargo in female synovial fluid may be due to a decline in estrogen levels. It is well known that declining estrogen levels are inversely related to increased incidence and severity of OA in females [ 49 , 50 , 51 , 52 ]. We previously demonstrated that estrogen inhibitor treatment alters miRNA cargo in female synovial fibroblast cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that differential EV protein cargo in female synovial fluid may be due to a decline in estrogen levels. It is well known that declining estrogen levels are inversely related to increased incidence and severity of OA in females [ 49 , 50 , 51 , 52 ]. We previously demonstrated that estrogen inhibitor treatment alters miRNA cargo in female synovial fibroblast cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results are opposite to those found by Bravo-José et al [14], who found a higher prevalence among female people (81.4%). It is known that female sex factors, such as menopause, increase risk of osteoporosis, as well as sarcopenia, besides a lower production of estrogen hormones [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…42 And the bioavailable testosterone which may contribute to the increase in muscle mass is decreased in elderly women. 43,44 Therefore, the decline of estrogen levels among elderly women and lower hemoglobin may have a synergistic effect on the health of muscle function and contributes to pathogenesis of frailty. However this possibility need more epidemiologic support.…”
Section: Discussionmentioning
confidence: 99%